From an allergic reaction to a superior vena cava syndrome - Milutinović Vojislava; Milutinović Vladimir (Halo 194)
Introduction/Objective: Superior vena cava syndrome (SVCS) is a collection of clinical signs and symptoms resulting from partial or complete obstruction of blood flow through the SVC. The venous obstruction may be due to compression, invasion, thrombosis, or fibrosis of the SVC. SVCS can be the initial presentation of a previously undiagnosed tumor in up to 60% of cases. We are presenting the case of a patient with SVC syndrome who was initially diagnosed with an allergic reaction. Case report: An eighty-year-old patient with an allergy diagnosis was referred from the Community Health Centre to the Internal Medicine Clinic. The patient had previously been treated with antihistamines for days due to swelling and facial redness, which showed no signs of improvement. During the chest x-ray, a widened shadow of the upper side of the mediastinum on the right side was noticed. Along with the clinical appearance of the patient, this raised doubts of the superior vena cava syndrome. Hence, the patient was hospitalised to the Department of Pulmonology. A CT chest scan showed an infiltrative change and a significantly compressed upper vena cava due to the mediastinal adenopathy. Urgent radiotherapy was prescribed to the patient. Conclusion: If primarily manifested by skin symptoms, the diagnosis of superior vena cava syndrome can be easily overlooked. It is often that the clinical picture is initially interpreted as an allergic reaction, asthma or airway obstruction. In the presented case, this rare syndrome was the first symptom of intrathoracic malignancy.